Correct Answer: \( \Large (2y - x)^{2} + y (16x + 5y) = \)

(1) \( \Large (2x + 3y)^{2} = 4x^{2} + 9y^{2} + 12xy \)

(2) \( \Large (2y - x)^{2} + y (16x + 5y) \)

= \( \Large 4y^{2} + x^{2} - 4xy + 16xy + 5y^{2} \)

= \( \Large x^{2} + 9y^{2} + 12xy \)

(3) 4x (x + 2y) + y (4x + 9y)

= \( \Large 4x^{2} + 8xy + 4xy + 9y^{2} \)

= \( \Large 4x^{2} + 9y^{2} + 12xy \)

(4) \( \Large (2x + 2y)^{2} - y (4x + 5y) \)

= \( \Large 4x^{2} + 4y^{2} + 8xy + 4xy + 5y^{2} \)

= \( \Large 4x^{2} + 9y^{2} + 12xy \)

(5) \( \Large (2x - y)^{2} + 8y (2x + y) \)

= \( \Large 4x^{2} + y^{2} - 4xy + 16 xy + 8y^{2} \)

= \( \Large 4x^{2} + 9y^{2} + 12xy \)

Thus, we see that except (2), other four expressions are equal